"Even though a lot of kids have it, not a lot of people have knowledge of it": A qualitative study exploring the perspectives of parents of children with cerebral/cortical visual impairment. (April 2023) - Oliver, Haley; Seccurro, Daria; Dorich, Jenny; Rice, Melissa; Schwartz, Terry; Harpster, Karen
Abstract: Background: Cerebral/Cortical Visual Impairment (CVI) is the leading cause of visual impairment in children and can negatively impact participation in daily activities. Methods and procedure: This qualitative study used virtual focus groups and an online questionnaire to understand the perspectives of families with children who have CVI. Constant comparison analysis was used to analyze focus group transcripts and extract themes. The PEDI-CAT and an online questionnaire were administered to characterize the study population. Outcomes and results: Four themes were identified: (1) Awareness of CVI and its effect on the child and family, (2) Parent experiences, (3) Child factors and functional implications, and (4) Supports that enhance child development/vision. Conclusions and implications: Findings from this study highlight the substantial impact that lack of CVI awareness had on parent experiences. Lack of awareness led to late diagnosis, missed intervention opportunities, and caregiver burden. Due to insufficient resources, parents had to educate themselves and service providers about CVI and advocate for their child's needs. Healthcare and educational providers who work with pediatric neurodevelopmental populations must be knowledgeable about clinical features of CVI, task and environmental adaptations to support vision and implementation of family-centered care. Highlights: Parents perceived lack of awareness of CVI among healthcare and education providers. Lack of awareness led to delays in receiving diagnosis and intervention. Parents educated themselves and providers about CVI. Children with CVI encountered challenges with daily activities per parent report. Children with CVI benefitted from vision-specific adaptations and interventions.